A model for the asymmetric lipid distribution in the human erythrocyte membrane. Issue 2 (February 1986) - Herrmann, Andreas; Müller, Peter
Abstract : The asymmetric transverse distribution of phospholipids in the human erythrocyte membrane can be explained by differences between the rate constants of flip and flop motion of the lipids. A selective interaction between aminophospholipids and spectrin does not need to be assumed for creating and maintaining the asymmetric localization of these lipids. Shape transformation of red cells could be caused by alterations of the flip-flop rate constants leading to a change of the lipid distribution and, consequently, to a differential area expansion of the outer and inner membrane leaflet.